2014
DOI: 10.3389/fncir.2014.00119
|View full text |Cite
|
Sign up to set email alerts
|

What can fish brains tell us about visual perception?

Abstract: Fish are a complex taxonomic group, whose diversity and distance from other vertebrates well suits the comparative investigation of brain and behavior: in fish species we observe substantial differences with respect to the telencephalic organization of other vertebrates and an astonishing variety in the development and complexity of pallial structures. We will concentrate on the contribution of research on fish behavioral biology for the understanding of the evolution of the visual system. We shall review evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 218 publications
(288 reference statements)
0
21
0
Order By: Relevance
“…Rosa Salva et al (2014) propose an alternative theory: perhaps these discrepant results could be a product of the intensive training procedure used. In support of this explanation, Rosa Salva et al (2013) implemented a more naturalistic training and testing protocol and found that 4-day-old chicks were susceptible to the Ebbinghaus illusion in the same direction as humans, contradictory to findings in six-month-old chickens by Nakamura et al (2008Nakamura et al ( , 2014.…”
Section: Does Visual (Mis)perception Differ Across Ecological Niches?mentioning
confidence: 99%
“…Rosa Salva et al (2014) propose an alternative theory: perhaps these discrepant results could be a product of the intensive training procedure used. In support of this explanation, Rosa Salva et al (2013) implemented a more naturalistic training and testing protocol and found that 4-day-old chicks were susceptible to the Ebbinghaus illusion in the same direction as humans, contradictory to findings in six-month-old chickens by Nakamura et al (2008Nakamura et al ( , 2014.…”
Section: Does Visual (Mis)perception Differ Across Ecological Niches?mentioning
confidence: 99%
“…The perception of illusory shapes and boundaries is the subject of two reviews/opinions (Agrillo et al, 2013 ; Rosa Salva et al, 2014 ) and one research article (Fuss et al, 2014 ). Based on the observation that different groups of teleost fish exhibit both modal and amodal completion (e.g., perception of illusory contours, as in the Kanizsa figures), Agrillo et al ( 2013 ) argue that fish represent an excellent experimental model for studying the development of gestalt principles of visual perception in newborn animals.…”
Section: Fish and Amphibian Studiesmentioning
confidence: 99%
“…Douglas et al 2003) and visual lateralization (e.g. Bisazza and Brown 2011;Rogers et al 2013). There are several adaptive ocular specializations found in fish (Fernald 1988), with some species possessing such inventive structures as eye heaters (Block 1986;Fritsches et al 2005), a tapetum lucidum or lens pigmentation (Hueter et al 2004;Douglas et al 1998).…”
Section: Introductionmentioning
confidence: 99%